Design of Energy-Efficient Protocol Stack for Nanocommunication Using Greedy Algorithms - Iqbal, Iqra; Nazir, Mohsin; Sabah, Aneeqa (Journal of Computer Networks and Communications, 2022)
With the passage of time, nanotechnology has become a mature discipline. It attracts attention of researchers toward nanocommunication and trying to give comprehensive set of tools to the engineering community. Nanonetwork contains nanosized communication devices that can be used in the field of military, bio medical, environment, ICT, and industry. Its communication abilities make this field powerful enough to make the devices interact with each other in the micro/macro world. The interconnection between nanonodes is not possible with the help of traditional networking techniques. In the upcoming years, nanotechnology is expecting to bring the integration of different nanodevices ranging from one to a few hundred of nanometers. This revolutionary transition is bringing Internet of Things (IoT) to Internet of Nanothings (IoNT). Due to its limited communication and computational capabilities, the energy availability in nanodevices is very scarce, which lead to various research challenges in the field of nanocommunication. The energy constraint narrows down the overall scope of nanocommunication. This research work will provide a step ahead and propose a design of energy-efficient routing protocol. The suggested solution will increase the effectiveness of nanocommunication techniques to achieve the maximum throughput by optimizing energy harvesting procedure. The comparison of devised solution and the state-of-the-art nanocommunication techniques will be established and evaluated through simulation. The results will be displayed and discussed to pave the way for future research in the domain of Internet of Nanothings (IoNT).